The Effect of Financial Literacy on Consumptive Behavior through Lifestyle and Financial Self-Control among Gen Z GoPay Users in Makassar City - Nurhidayah, Nurhidayah; Hidayat, Andi; Indriani, Dian; Liong, Harlina; Sani, Amar (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2025)
This research aims to examine the influence of financial literacy on the consumer behavior of GoPay service users among Generation Z in Makassar City, with lifestyle and financial self-control as mediating variables. Using a quantitative approach and structural equation modeling (SEM-PLS) with 159 respondents, the findings reveal that financial literacy significantly affects both lifestyle and financial self-control. However, financial literacy does not have a direct significant effect on consumptive behavior. Instead, lifestyle and financial self-control mediate the relationship, serving as key pathways through which financial literacy impacts consumer behavior. The results underscore the importance of targeting not only knowledge but also behavioral and lifestyle factors in order to effectively manage and reduce consumptive tendencies among digital payment users. These findings highlight the necessity of comprehensive financial education programs that integrate cognitive, behavioral, and contextual aspects for Generation Z in the digital era.